Further characterization of heart - and skeletal muscle-specific mitochondrial aspartyle -tRNA synthetase (DARS2) knockout mouse - Kartal, Özlem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Mitochondrial respiratory chain defects are the primary cause of mitochondrial disorders. Mitochondria have developed various adaptive responses to counteract the effects of these defects. In this study, the heart- and skeletal muscle-specific mito chondrial aspartyl-tRNA synthetase (DARS2) knockout mouse model (hmKO) was further characterized phenotypically and molecularly by previously unchecked param eters. Phenotypic characterization demonstrated that hmKO mice have lower exercise performance, poorer coordinated activity, and weaker muscles than their wild-type lit termates. Furthermore, respiratory chain deficiency led to mitochondrial dysfunction exemplified by reduced oxygen consumption rate, reactive oxygen species (ROS) flux, and ATP production. In addition, components of the mitochondrial integrated stress response (ISRmt) were upregulated, while the antioxidant response was downregulated in the heart. Although there is no specific cure for mitochondrial diseases, various ap proaches can slow down the disease progress or attenuate the symptoms, one of which is ketogenic diet (KD). Animals were fed with KD to mitigate the effects of the severe phenotype of hmKO mice. Unfortunately, KD could not prolong the shortened lifespan and improve the exercise performance and muscle strength of hmKO animals due to our model’s severe diseased phenotype.
Keywords: Mitochondrial DNA -- Abnormalities.; Mitochondrial pathology.